EXÁMEN ESPECIAL AL RUBRO ACTIVO CORRIENTE EN LA COOPERATIVA DE AHORRO Y CRÉDITO “MARCABELÍ” LTDA. PERIODO 2021 - Olaya Vélez, Elyn Benedetta (2024)
The present work of curricular integration entitled "Special Examination to the Current Assets Item in the Cooperative de Ahorro y Crédito Marcabelí LTDA. Period 2021" was developed based on the proposed objectives which are oriented to the evaluation of the internal control implemented for the current assets of the cooperative in order to determine the degree of soundness, effectiveness and administrative efficiency, verify compliance with applicable regulations, determine the reasonableness of the balances of the accounts of the examined component and issue a special examination report in order to make known the results, observations and recommendations to serve as a basis for taking the right actions in the Cooperative. To develop these objectives, the financial audit process was used in its planning, execution and communication of results phases. First, the necessary tools were prepared for the evaluation of internal control, such as work papers, among which are: employment contract, work order, notification of the start of a special examination, then the pre- and post-visit guide was prepared. For this purpose, the audit programs were prepared for each component, the internal control questionnaire was applied for its evaluation within the cooperative. Once the data was obtained, the findings were identified with their respective comments, conclusions and recommendations, once this information was obtained, the special examination report was prepared, through which the following results were announced: The credits offered are not governed by the segments established by the Superintendency of Banks and Insurance (SBS), but rather they conform to the segmentation, amount and maximum reference rates established by the Central Bank of Ecuador (BCE). Bad debts exceed 10% of the total portfolio. Accounts receivable reports are not prepared monthly by age of balances, for the adoption of decisions related to collection management. Bank reconciliations do not have the signatures of the corresponding personnel.